Epileptic seizures as a predictive factor for mortality in patients with aneurysmal subarachnoid hemorrhage: a retrospective cohort study - Solari, Matías; Mule, Agustín; Moine, Andrés; Seraglio, Florencia; Bulacio, José; Palazzolo, Esteban (Revista Argentina de Neurocirugía, 2025)
Background: aneurysmal subarachnoid hemorrhage (SAH) is a prevalent condition, especially in regions such as Latin America, with a global in-hospital mortality rate of 20%. 26% of patients with SAH present with seizures, leading current guidelines to recommend the prophylactic use of antiepileptic drugs (AEDs) in certain situations. Objectives: to determine the presence of epileptic seizures and the mortality rate in patients hospitalized with a diagnosis of subarachnoid hemorrhage (SAH) secondary to aneurysmal rupture. Methods: a retrospective analytical observational study was carried out in a cohort of patients hospitalized in our institution with a diagnosis of SAH secondary to aneurysmal rupture who suffered epileptic seizures during hospitalization and the associated mortality rate was analyzed in a 5-year period (2020-2024). IBM SPSS® (v30.0.0) was used for descriptive statistics, Chi-square test (χ²), T-test and ANOVA for group comparison and logistic regression to identify predictors of mortality. Results: the study included 45 patients, with a predominance of women (73%) with a mean age of 58 years. 29% of patients had epileptic seizures during hospitalization. Overall mortality was 60%, and patients who experienced seizures had a significantly higher mortality rate (85% / p = 0.013) compared to those who did not have seizures. Conclusions: the results suggest a statistically significant correlation between the presence of epilepsy and mortality in patients with aneurysmal SAH. Although the presence of epileptic seizures in these patients is relatively frequent, this finding underlines the need for further studies to identify specific factors that contribute to increased mortality in this clinical context.